Dampak kinerja keuangan terhadap harga saham emiten kategori indeks LQ45 (studi empiris, 2019-2021) - Puspitasari, Ika; Pratama, Alief Indra (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to obtain empirical evidence and analyze the impact of financial performance on stock prices of issuers listed in the LQ45 category. The data used as a sample in this study is secondary data in the form of annual financial reports. The subjects of this survey are companies listed on the Indonesia Stock Exchange (IDX) and included in the LQ45 index for three consecutive years from 2019 to 2021. As the name implies, the LQ45 Index consists of 45 issuers with high stock liquidity scores and were selected based on some criteria. This indicator is used as research material for the company's stock trading. Companies included in the LQ45 index are the stocks that are most in demand by investors because of their large capital and frequent stock trading. It attracts investors because their finances are considered good and they have attractive growth prospects. Data analysis was performed by descriptive statistical analysis, classical assumption test and hypothesis testing with multiple linear regression analysis. The results of this study are intended to determine whether liquidity (current ratio), profitability (return on assets) and Net Profit margin (NPM) have a positive effect on stock prices.